2016
DOI: 10.1021/acs.bioconjchem.6b00598
|View full text |Cite
|
Sign up to set email alerts
|

Coordination to Imidazole Ring Switches on Phosphorescence of Platinum Cyclometalated Complexes: The Route to Selective Labeling of Peptides and Proteins via Histidine Residues

Abstract: In this study, we have shown that substitution of chloride ligand for imidazole (Im) ring in the cyclometalated platinum complex Pt(phpy)(PPh)Cl (1; phpy, 2-phenylpyridine; PPh, triphenylphosphine), which is nonemissive in solution, switches on phosphorescence of the resulting compound. Crystallographic and nuclear magnetic resonance (NMR) spectroscopic studies of the substitution product showed that the luminescence ignition is a result of Im coordination to give the [Pt(phpy)(Im)(PPh)]Cl complex. The other i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(54 citation statements)
references
References 90 publications
6
48
0
Order By: Relevance
“…The discrepancy of the three complexes in anti-proliferative activity between both cell lines might result from their difference in cellular uptake and/or genomic DNA binding efficiency, since platinum DNA-adducts have been recognized as the ultimate event generated in cells [39,50]. At the stage, we want to point out that contrary to other platinum complexes, our complexes are not luminescent [51].…”
Section: Cellular Uptake and Genomic Dna Binding Of Platinum Complexesmentioning
confidence: 91%
“…The discrepancy of the three complexes in anti-proliferative activity between both cell lines might result from their difference in cellular uptake and/or genomic DNA binding efficiency, since platinum DNA-adducts have been recognized as the ultimate event generated in cells [39,50]. At the stage, we want to point out that contrary to other platinum complexes, our complexes are not luminescent [51].…”
Section: Cellular Uptake and Genomic Dna Binding Of Platinum Complexesmentioning
confidence: 91%
“…However, although promising, metal complexes are generally only less developed as pharmaceutics owing to their poor water solubility and limited cellular uptake [30] . One way to overcome these issues is the combination of metal complexes with bioactive peptides, which has gained considerable attention during the last decade [31–41] . In this context, so‐called cell‐penetrating peptides (CPPs) are promising tools to deliver metal complexes into various types of cells [41–49] .…”
Section: Introductionmentioning
confidence: 99%
“…21,22,26 Recently, we published the study on the reactions of [Pt(ppy)(PPh 3 )Cl] (ppy-2-phenilpyridine) complex with imidazole (Im), histidine, and histidine-containing proteins (human serum albumin (HSA) and ubiquitin (Ubq)). 27 The study revealed that the reaction of this complex with imidazole and imidazole function of histidine results in substitution of the chloride ligand to give the cationic complexes of the following composition [Pt(ppy)(PPh 3 )(Im)] + . In contrast to nonluminescent starting compound, the substituted products are phosphorescent and demonstrate appreciable quantum yield and emission in the green region of visible spectrum (at ca.…”
Section: ■ Introductionmentioning
confidence: 99%